PERSPEKTIF KONSELOR ISLAMI TERKAIT TRANFORMASI DAKWAH DALAM MENANGANI KRISIS RUMAH TANGGA DAN TOXIC RELATIONSHIP - Apriari , Shinta Ath Thariq; Wahyuni, Siti Aisyah; Delvani, Rina (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2025)
Domestic crises and the phenomenon of toxic relationships are increasingly complex issues in the modern era, characterized by increasing conflict, verbal and emotional violence, and couples' inability to manage differences. This situation demands the presence of Islamic counselors to provide a more transformative approach to da'wah (Islamic outreach). Da'wah transformation is considered crucial because it can provide solutions that not only emphasize the spiritual dimension but also address psychological and social aspects. This study used qualitative methods with data collection techniques through semi-structured interviews and indirect observation, and involved five Islamic counselors actively providing family counseling services. The sample collection was analyzed using a purposive sampling technique. Data analysis was conducted using a thematic analysis approach to explore in-depth the counselors' experiences and strategies in handling cases. The results show that Islamic counselors interpret da'wah transformation as a process of family empowerment through the integration of applicable spiritual, psychological, and social values. The strategies used include strengthening spiritual communication between couples, moral guidance as a basis for building relationship ethics, and the application of religious coping-based counseling. These strategies have proven effective in reducing conflict, improving communication quality, and preventing the negative impacts of toxic relationships.   Keywords: transformation da’wah, toxic relationship, Islamic counselor.